Modelling of the Earth's transmission spectrum in the framework of one-slab model - Pavlenko Ya V.; Polinovskyi G.; Martin E.L. (EPJ Web of Conferences, 2013)
We discuss the possibility of using the transmission spectrum of the Earth in the measurements of the molecules abundance ratios. We use optical and near infrared transmission spectrum of the Earth obtained during observations of a lunar eclipse in 2008 by Enric Palle and others (E. Pallé et al., 2009). This task is interesting in terms of estimation of the chemical composition of the Earth-like planets around other stars during their transits. We use one-slab model approach for modelling transmission spectra using HITRAN line database. Comparison with observational data gives us clues to our problem.